The impact of local development project on social capital: evidence from the Bohol irrigation scheme in the Philippines - Park, Hogeun; Tsusaka, Takuji; Pede, Valerien; Kim, Kyung-Min (MDPI, 2017)
The purpose of this paper is to investigate the connection between local development projects and the residents’ social capital in Bohol, The Philippines. From this perspective, we hypothesized that social behaviors of local farmers are influenced by the availability of canal irrigation due to the collective water management required in irrigated societies. By combining the results of the ultimatum game (UG) with a household survey on 245 villagers in Bohol, this paper (1) measures the degree of social capital at the individual level and (2) quantifies the effects of irrigation on social capital by controlling household as well as individual characteristics. Moreover, we employed a Spatial Autoregressive model to explore the spatial effects and social contexts of farmers’ behavioral patterns. The empirical results show that the level of measured social behavior is strongly associated with access to community irrigation water and asset holdings. Additionally, increased physical distance between residents leads to a decrease in social capital, or interdependency, among them. The results suggest that community engagement (e.g., irrigation management committee and turnout service association) with local development projects would not only improve agricultural productivity but also enhance social relationships among farmers, highlighting its importance.